KARAKTERISTIK DAN FUNGSI QIRA’AH DALAM ERA LITERASI DIGITAL - Ahmad Nurcholis; Syaikhu Ihsan Hidayatullah; Muhamad Asngad Rudisunhaji (El-Tsaqafah : Jurnal Jurusan PBA, 2019)
This article described and analyzed the characteristics of qira’ah and itsfunctions in this digital literacy era. The need toward learning qira’ah (reading)by using computers and social media is high. The Arabic learning then adjustwith Industrial Revolution 4.0 especially in learning qira’ah (reading). The use ofInternet of Things (IoT), big data, cloud databases, block chain, and others willchange the learning design of qira’ah from paper-based to paperless. The researchersuse qualitative approach to produce the descriptive data. The results showed that thecharacteristics of qira’ah emphasize on the aspects of analysis and understanding ofwhat is read, not on how to read. While the function of qira’ah in digital literacy erais the high quality of digital based literacy which is oriented not only on the religiousfield but also on academic, professional / practical, economic, and ideology